Microstructural evolution and deformation behavior of Al-Cu alloys: A Transmission X-ray Microscopy (TXM) and micropillar compression study. (1st February 2018) - Kaira, C. Shashank; Kantzos, Christopher; Williams, Jason J.; De Andrade, Vincent; De Carlo, Francesco; Chawla, Nikhilesh
Abstract: A unique approach to correlating an evolving 3D microstructure in an Al-Cu alloy and its micro-scale mechanical properties has been introduced. Using these nanoscale three-dimensional microstructures derived from Transmission X-ray Microscopy (TXM), individual contributions from different strengthening mechanisms were quantified. The spatial distribution and morphology of the individual θ′ and θ phases were seen to play an important role in influencing dislocation storage. Uniaxial micro-compression experiments were used to quantify the stress-strain response of the alloy at different aging times. Transmission electron microscopy (TEM) aided in discerning dislocation activity at these precipitates. A model is proposed to accurately predict the variation in yield stress by using appropriate morphological parameters from the 3D microstructure and its validity has been corroborated using experimental measurements. Distributions of 2D and 3D inter-precipitate spacing were seen to provide crucial insights on influencing deformation in such precipitation-strengthened alloys. Finally, the transition in deformation behavior and origin of numerous strain bursts were investigated using in situ micropillar compression testing. Graphical abstract: Image 1